KEANEKARAGAMAN JENIS BURUNG DI HUTAN KOTA PEKANBARU - Hadinoto Hadinoto; Aras Mulyadi; Yusni Ikhwan Siregar (Jurnal Ilmu Lingkungan, 2012)
A bird is a wildlife which could be found almost in any vegetated environment. The existenceof a bird in one area is very important because it could affect the presence and distribution ofplant species. The research aims to identify species diversity, distribution of bird species,habitat and analyze the relationship of bird species diversity to habitat in urban forest,Pekanbaru Municipal. The research was held in Diponegoro Urban Forest, Arboretum ofForestry Training Hall and Arboretum of Lancang Kuning University. The research wasconducted from March to June, 2011. All bird data were collected using a point countmethod. The vegetation data collected included species, composition and structure byforming a plot measuring. It was found 45 species, 26 families and 10 orders of birds. Thebird species diversity indices (H’) varied between 2.85 and 3.29, the bird average indices (E)varied between 0.87 and 0.9 and species richness indices (R) between 4.67 and 6.70. Thevertical bird distribution was mostly the bird with the upper canopy (35%), middle canopy(34%) and the rest was lower canopy (16%) as well as ground surface (15%). It was alsofound 77 tree species of 30 families. The tree species diversity indices (H’) varied between2.06 and 3.23, the species average indices (E) was between 0.64 and 0.85 and speciesrichness indices (R) was between 4.29 and 7.29. the bird species diversity in Pekanbaru urban forest had a positive correlation to the urban forest making trees.